Development of brain-based learning teaching materials using crossnumber games in mathematics - Pebrianti, Adella; Caria, Rahayu; Maryono, Iyon (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2024)
Based on the results of the analysis of MTSN 2 Bandung, by using the learning media of the Ale application, the researcher developed teaching materials as a reference for learning media. Brain-Based Learning Teaching Materials Using Crossnumber Puzzle Games are developed using the Brain Based Learning approach. This research aims to find out: (1) the process of developing teaching materials; (2) the validity of the material; (3) material practicality; (4) the effectiveness of teaching materials. This method is used by the R&D Method with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. The results of the study show that the validity of the media is very valid in the media aspect by media experts and the material aspect is in the valid category by material experts. Practicality of the media gets a very practical media category Effectiveness gets very effective results with a high category. However, there are shortcomings in teaching materials such as crossnumber practice problems cannot be used repeatedly, there is an assumption that students who do crossnumber may not necessarily be able to solve the problem, because crossnumber can use intuition.